Critical Analysis of Laboratory Automation and Its Role in Quality Assurance - Alreshidi, Bander Saad; Rasheedi, Mousa Hamad Muatiq; Alrasheedy, Abdullah HAjaj Hejji; Nidaa, Saud Abdullah; Alreshidi, Abdulrahman Magbool; Alsudayri, Hamoud Abdulaziz; alreshidi, Naif khidhran; Alrashidi, Hameed Maedh; Almuthebry, Abdulaziz Musleh; Alreshidi, Turki Ali K (Journal of Ecohumanism, 2024)
Automation in laboratories has enhanced operations as a diagnostic tool to reveal accuracy, efficiency, and all-around quality in laboratories. The automation of specimens in the management of laboratories is shed light on in this review, focusing on increased efficiency, less human interference for increasing errors, and quality control as a number one priority. Automated liquid handling RFs, robotic systems, laboratory information management systems (LIMS), and point-of-care automation devices have been consistently found to enhance diagnostics and efficiency. However, contradictions have included high initial investment, integration into existing systems, and a major concern of staff training as factors that hinder organizations from adopting them. This paper presents a thorough literature review on laboratory automation, assessing the benefits and drawbacks of the solution concerning quality assurance and suggesting ways to enhance the practical application of the solution in clinical laboratories.